2019
DOI: 10.1111/tbed.13196
|View full text |Cite
|
Sign up to set email alerts
|

Survey for Hepatitis E virus infection in non‐human primates in zoos in Spain

Abstract: Summary Hepatitis E virus (HEV) is an emerging zoonotic pathogen that has been detected in different animal species. A survey study was carried out to assess HEV infection in non‐human primates (NHPs) housed in zoos in Spain. Anti‐HEV antibodies were detected in eight of the 181 NHPs tested (4.4%; 95%CI: 1.4–7.4). At least one seropositive animal was detected in five of the 33 species sampled (15.2%). This is the first report of seropositivity in black‐and‐white ruffed lemurs (Varecia variegata), common chimpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…These results, coupled with the presence of anti‐HEV antibodies in a yearling Iberian wolf in zoo E in 2014, suggest HEV circulation in zoo animals from these zoos during the study period. Previously detected seroconversion in a common chimpanzee from zoo E between 2015 and 2016 supports this hypothesis (Caballero‐Gómez et al., 2019b ).…”
Section: Resultssupporting
confidence: 54%
“…These results, coupled with the presence of anti‐HEV antibodies in a yearling Iberian wolf in zoo E in 2014, suggest HEV circulation in zoo animals from these zoos during the study period. Previously detected seroconversion in a common chimpanzee from zoo E between 2015 and 2016 supports this hypothesis (Caballero‐Gómez et al., 2019b ).…”
Section: Resultssupporting
confidence: 54%
“…In connection with this, 52 (19.7%) of 264 wild boars sampled in metropolitan areas of Barcelona (northeastern Spain) were positive for HEV RNA (Wang et al, 2019), indicating a potential source of HEV transmission in urban areas. In our study region, HEV circulation has been reported in wild boar populations with prevalence values ranging between 6.8% and 23.2% (Risalde et al, 2017;Rivero-Juarez et al, 2018) and HEV exposure has also been detected in other mammals, including zoo animals and humans (Caballero-Gómez et al, 2019;Rivero-Juarez et al, 2015). In any case, additional studies are needed to determine the sources of HEV transmission in cat and dog populations in the study area.…”
Section: Resultsmentioning
confidence: 85%
“…Furthermore, a serological study in Iberian red deer carried out in Spain detected IgG anti-HEV in 10.4% (101/968) of animals (Mariana Boadella et al, 2010 ). A serosurvey of HEV infection was carried out in non-human primates from zoos of Spain, revealing a prevalence of IgG ani-HEV of 4.4% (8/181) (Caballero-Gómez et al, 2019b ). Moreover, a serological survey in dogs and cats in Spain was conducted in Cordoba, having anti-HEV antibodies been detected in 9.9% (15/152) of dogs and in 2.8% (4/144) of cats (Caballero-Gómez et al, 2022b ).…”
Section: Resultsmentioning
confidence: 99%